Dayswork : a novel - Bachelder, Chris; Habel, Jennifer (W. W. Norton & Company, 2023)
"Dayswork tells the story of a woman who spends the endless days of the pandemic sorting fact from fiction in the life and work of Herman Melville. Obsessed by what his devotion to his art reveals about cost, worth, and debt, she delves into Melville's impulsive purchase of a Massachusetts farmhouse, his fevered revision of Moby-Dick there, his intense friendship with neighbor Nathaniel Hawthorne, and his troubled and troubling marriage to Elizabeth Shaw. As the narrator's fascination grows and her research deepens, she examines Melville's effect on the imagination and lives of generations of biographers and writers, including Elizabeth Hardwick and Robert Lowell. Ultimately, her quarantine project is a midlife reckoning with her own marriage and ambition."--